Interrogating the Contending Issues and Challenges Confronting Investment Opportunities and Ease of Doing Business in Nigeria (2015-2025) - Yusuf Garba Manjo (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2025)
Nigeria's economy holds the largest market in Africa and presents significant opportunities for local and international investors. However, the ease of doing business in Nigeria has become a national issue in the last decade due to the World Bank's ease of doing business index, which has been poor in areas with productive sectors, affecting investment. This study critically examines the contending issues and persistent challenges confronting investment opportunities and the ease of doing business in Nigeria between 2015 and 2025. This study examines the impact of institutional, infrastructural, security, and policy-related factors on Nigeria’s investment environment over the last ten years. The study employs a qualitative approach supported by empirical data, policy reviews, and stakeholder perspectives to examine the challenges related to investment and the ease of doing business in Nigeria. It evaluates the effectiveness of various reforms in the business environment. It analyses how these reforms have resulted in measurable enhancements in the ease of business over the past decade. The results indicate a notable disparity between the objectives of policies and their actual implementation, as numerous enterprises continue to face challenges due to inadequate infrastructure, insecurity, excessive taxation, inconsistencies in regulations and corruption. The study concludes by offering policy recommendations geared towards enhancing transparency, strengthening institutions, and fostering a more enabling and secure environment for sustainable investment and ease of business in Nigeria.